ONLINE BUYING AND SELLING SYSTEM OF DROPSHIPPING AND RESELLING IN THE PERSPECTIVE OF STATUTORY REGULATIONS AND ISLAMIC ECONOMIC FATWAS - Candrawati, Iin; Hafith , Muh. Abdulloh; Robbani , Shofa; Huda , Nurul (Universitas Muhammadiyah Surabaya, 2025)
The rapid growth of digital commerce in Indonesia has encouraged the emergence of innovative business models such as dropshipping and reselling. This study aims to analyze the legal status of dropshipping and reselling systems under both Indonesian statutory regulations and Islamic economic fatwas. Using a qualitative normative legal research approach, the study applies statute, conceptual, and comparative analyses of the Consumer Protection Law, Electronic Transaction Law, and related DSN-MUI Fatwas. The findings show that Indonesian positive law recognizes dropshipping and reselling as lawful business activities when they adhere to transparency, accountability, and consumer protection principles. The study concludes that harmonization between national regulations and Islamic economic fatwas is essential to ensure that digital trade operates within a framework of both legal enforceability and moral ethics. An integrative approach combining statutory compliance and Sharia principles can strengthen justice, fairness, and transparency in Indonesia’s digital economy. This study contributes to the development of digital commerce law by offering an integrative model between statutory enforceability and Islamic ethical legitimacy.